KARAKTERISTIK DAN MOTIVASI WISATAWAN MANCANEGARA BERKUNJUNG KE PANTAI JEMELUK-AMED, DESA PURWAKERTI, KECAMATAN ABANG, KARANGASEM - Cahyana, Helmi; Suwena, I Ketut; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2018)
Jemeluk-Amed Beach is a marine tourism destination in the Purwakerti Village . Marine tourism which has a potential in variety of coral reef maintained continuity. Jemeluk-Amed beach has a wide range of tourism activities such as snorkeling, diving, canoeing, and sailing. Travelers who come to visit Jemeluk-Amed Beach certainly has the characteristics and motivations are different from each other. The purpose of this study was to determine the characteristics and motivations of foreign tourists who visited Jemeluk-Amed Beach, Karangasem. The method used to determine the rating by trip characteristics and tourist descriptor, while the tourist motivation is classified into four groups: the physical motivation, cultural motivation, social motivation, motivation fantasy. A total 110 questionnaire were distributed by field research to tourist as a respondent. The results of the questionnaire then processed quantitative presented in the form of tables and analysis of qualitative data in the form of a narrative text according to the research objectives. The research results showed that foreign tourists visited Jemeluk-Amed Beach is dominated by tourists from The Europe Continent with an average age of 26-35 years (53.64%); the average length of stay 1-3 days (78.18%); most of travelers visited is drifter tourists. Tourist motivation mostly physical stated motivation as a reason to visited; partly motivated to exercise (sports) as much as 40.91% of the overall respondents. Travelers visited for fun (28.18%) of the overall respondents. Suggestions of this study are expected to be contribute ideas to The Government of Karangasem and for groups of fishermen Tunas Mekar and Mina Prami.